Intelligent Fault Detection and Isolation System in Wireless Sensor Networks: A Review - Hadi, Mohammed H.; Alaa Sabri, Atheer.; Issa, Abbas Hussain . (International Journal of Psychosocial Rehabilitation, 2020)
wireless sensor networks (WSNs) have been the subject of investigation in the previousyears; networks fault diagnosis obtained considerable notice. Fault diagnosis a fundamental element for wireless networks, particularly in WSNs, due to their ad-hoc essence, limited resources and deployment conditions. WSNsusually made of 100s of nodes that are used in comparatively rigid and difficult conditions. In aspects of hardware value, sensor nodes constantly employ moderately inexpensivechips that tenders those nodes become faulty or error-prone during their lifespan. Electromagnetic interference and natural factors can further impact the WSNs performance. To enhance data quality, increase network security, reduce response time, and increase network lifespan, numerous researches have concentrated on WSNs faults diagnosis. This review labels fault diagnosis techniques in the recent years to three classes according to key attributes and decision centers of working algorithms: distributed, centralized, as well as hybrid methods. All those researches have particular aims, this paper attempts to analyze them.